The Use of Nursery Rhymes to Improve Young Learners’ English Listening Skills at Primary Education - Raiamanda, Ismi; Gailea, Nurhaeda; Utomo, Dhafid Wahyu (Journal of Linguistics, Literacy, and Pedagogy, 2024)
This research aims to find out how the process of the use of nursery rhymes improves young learners’ English listening skills, to find out the result of the use of nursery rhymes to improve young learners’ English listening skills and to discover why nursery rhymes can improve young learners’ English listening skills. This research was conducted at the elementary school level in the fourth grade of SDN Tunjung 1. Classroom action research with two cycles of quantitative and qualitative design was applied in this research. The data analysis was calculated in each cycle of the pretest and post-test, with 75 as the KKM score. The result of pre-test mean score in the first meeting of cycle I was 78,7, while the post-test meeting was 83,5. Then, the pre-test mean score in the first meeting of cycle II was 80, while the post-test meeting was 88,7. There are 18 students, or 78,26%, who passed KKM cycle I, 19 students or 82,60%, who passed KKM in the pre-test of cycle II, and 20 students or 86,95%, who passed KKM in the post-test of cycle II. The researcher concluded that the students improved by using nursery rhymes to learn English listening skills in the classroom.